226k views
4 votes
How is the graph of the quadratic function to produce the graph of y=-(2x+6)^2+3

User Alberte
by
4.9k points

1 Answer

2 votes

Answer:

The graph in the attached figure

Explanation:

we have


y=-(2x+6)^(2)+3

Factor the leading coefficient


y=-(2(x+3))^(2)+3


y=-4(x+3)^(2)+3

This is the equation of a vertical parabola in vertex form

The parabola open downward

The vertex is a maximum

The vertex is the point (-3,3)

Find out the x-intercepts (values of x when the value of y is equal to zero)

For y=0


0=-4(x+3)^(2)+3


4(x+3)^(2)=3


(x+3)^(2)=(3/4)

square root both sides


(x+3)=(+/-)(√(3))/(2)


x=-3(+/-)(√(3))/(2)


x1=-3+(√(3))/(2) ----->
x1=-2.134


x2=-3-(√(3))/(2) ----->
x2=-3.866

using a graphing tool

The graph in the attached figure

How is the graph of the quadratic function to produce the graph of y=-(2x+6)^2+3-example-1
User Nitzmahone
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.